Studi Kasus Peran Pustakawan dalam Penerapan Open Access di Perpustakaan UIN Malang - Dian Novita Fitriani (ACARYA PUSTAKA, 2017)
AbstrakThe development of Open Access (OA) in Indonesia, especially in the academic library shows a fairly slow development. Obstacles to the development of OA are not technically, legally or economically, but more of a cultural constraint. UIN Malang Library is a university that develops both in Indonesia until now very concerned about OA. But in its development, development of OA in UIN Malang get obstacles, especially from the environment of academicians and leaders. By using Giddens' structural analysis, this research aims to see the role of librarian in developing OA in UIN Malang. This study uses a critical paradigm with qualitative research methods and case study approaches. From the results of the research found that librarian UIN Malang as an agent able to do the agency to the current structure. By holding the principles of OA, librarians make various efforts to provide understanding to the campus management and academic community to understand the "spirit" of OA as an alternative to scientific communication that has a significant role in the process of scientific communication especially within the scope of universities.Keywords: Librarian, Open Access, Institutional Repository